2021
DOI: 10.1002/cctc.202101107
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of Catalytic Nucleophile of β‐Galactosidase Retains Residual Hydrolytic Activity and Affords a Transgalactosidase

Abstract: Glycosidases that cleave oligosaccharides can also synthesize the glycosidic bond. Site-directed mutagenesis of the catalytic nucleophile commonly abolishes their hydrolytic activity, affording glycosynthases that use glycosyl fluorides as substrates.Here, the synthetic ability of β-galactosidase from Bacillus circulans isoform A (BgaD-A; EC 3.2.1.23, GH2) was investigated by site-directed mutagenesis. The cold-shock expression ensured selective induction and correct folding. Three mutants were constructed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…For structural analysis see the Supporting Information, Table S2, Figure S3a-S3d for compound 3; Table S3, Figure S4a-S4d for compound 4. (6,7,8) Compound 6 (LacNAc-N 3 , β-D-galactopyranosyl-(1→4)-2-acetamido-2-deoxy-β-Dglucopyranosyl azide) was synthesized as described previously [31]. Briefly, the glycosyl donor pNP-β-Gal (5; 30 mM, 36 mg) and the acceptor GlcNAc-N 3 (1; prepared as described previously [30]; 150 mM, 148 mg) were suspended in 50 mM sodium phosphate buffer pH 6.0, and β-galactosidase BgaD-A (252 µg, 2.4 U, 260 µL) was added.…”
Section: Synthesis Of (2-acetamido-2-deoxy-β-d-glucopyranosyl) N Azid...mentioning
confidence: 99%
See 2 more Smart Citations
“…For structural analysis see the Supporting Information, Table S2, Figure S3a-S3d for compound 3; Table S3, Figure S4a-S4d for compound 4. (6,7,8) Compound 6 (LacNAc-N 3 , β-D-galactopyranosyl-(1→4)-2-acetamido-2-deoxy-β-Dglucopyranosyl azide) was synthesized as described previously [31]. Briefly, the glycosyl donor pNP-β-Gal (5; 30 mM, 36 mg) and the acceptor GlcNAc-N 3 (1; prepared as described previously [30]; 150 mM, 148 mg) were suspended in 50 mM sodium phosphate buffer pH 6.0, and β-galactosidase BgaD-A (252 µg, 2.4 U, 260 µL) was added.…”
Section: Synthesis Of (2-acetamido-2-deoxy-β-d-glucopyranosyl) N Azid...mentioning
confidence: 99%
“…The synthesis of ligand 6 (LacNAc-N 3 ) was essentially performed as described previously [31]. For the galactosylation reaction, pNP-β-Gal (2) was used as a glycosyl donor and GlcNAc-N 3 (1) as an acceptor.…”
Section: Chemo-enzymatic Synthesis Of Azido-functionalized Carbohydra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in many prepared variants, the significant increase in selectivity (GalNAcase/GlcNAcase activity ratio decreased from 3- to 8-fold compared to WT) has not caused a considerable decline in specific activity as is otherwise usual in active site mutant variants, particularly those at the catalytic nucleophile [ 51 ]. Here, in many cases, we rather observed an increase in the enzyme specific activity compared with the WT.…”
Section: Resultsmentioning
confidence: 99%
“…Given the versatility of β-galactosidase from Bacillus circulans mutant (BgaC), P. Bojarová et al [73] reported the synthetic application of these mutant enzymes for the transformation of α-galactosyl fluoride (αGF) and β-galactosyl azide (βGN3) α-galactosyl to test the glycosynthase activity. Those three different mutants were obtained using selective mutagenesis, via active site modification to glycine, alanine, and threonine, and they were then applied in the transformation.…”
Section: Galactosynthasesmentioning
confidence: 99%